Kepemilikan Manajerial, Kebijakan Dividen, Leverage, Profitabilitas, Ukuran Perusahaan, dan Nilai Perusahaan (Studi pada Perusahaan Pertambangan di Indonesia) - Marhaeningtyas, Dian; Hartono, Ulil (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This study aims to examine and understand the effect of managerial ownership, dividend policy, leverage, profitability, and company size on the value of the mining sector listed on the Indonesia Stock Exchange period 2015-2018. This type of research is causal research and the data is quantitative sourced from the IDX web. The sampling method uses purposive sampling to obtain 16 companies that fit the criteria. Data analysis uses multiple linear regression. The test results explained that the independent variables simultaneously influence the dependent variable. Partial test results explain that leverage has a positive effect on firm value because the company's ability to pay obligations in the future will get a positive response from the market. Profitability has a positive effect on firm value because the increase in profits shows the company's ability to use its resources. The results of this study indicate that leverage and profitability have a significant positive effect on a firm’s value, while managerial ownership, dividend policy, and firm size has no significant effect on a firm’s value.